Implementation of Mobile-Based Inventory Management System to Improve Stock Accuracy in SMEs - Harahap, Ricky Ramadhan; Supiyandi, Supiyandi; Rizal, Chairul (Raskha Media Group, 2026)
The SME partner faced significant issues with manual stock recording, resulting in discrepancies, delayed reporting, and input errors. This community service activity aimed to implement a mobile-based inventory management system to improve stock accuracy and operational efficiency. The methods included needs assessment, system design, cloud-based mobile deployment, training for 12 employees, and evaluation using the Stock Accuracy Rate and transaction recording time. The results showed an increase in stock accuracy from 83% to 96%, a reduction in stock discrepancies from 17% to 4%, and a decrease in recording time from 9 minutes to 3 minutes per transaction. The system enabled real-time reporting and automatic minimum stock notifications. The implementation significantly enhanced operational efficiency and data-driven decision-making.